2011
DOI: 10.1055/s-0029-1246072
|View full text |Cite
|
Sign up to set email alerts
|

Clinical MR Mammography: Impact of Hormonal Status on Background Enhancement and Diagnostic Accuracy

Abstract: In premenopausal women, HS leads to increased BE of breast tissue, independent of CP. Distinct BE and less pronounced, non-optimal CP may lead to an increased number of false positive findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 15 publications
1
36
1
4
Order By: Relevance
“…Enhancement was highest during weeks 1 and 4 and lowest during week 2. Our results are consistent with those of previous studies (9,10,(16)(17)(18). This is not surprising, because we know that BPE depends on hormonal changes.…”
Section: Discussionsupporting
confidence: 94%
“…Enhancement was highest during weeks 1 and 4 and lowest during week 2. Our results are consistent with those of previous studies (9,10,(16)(17)(18). This is not surprising, because we know that BPE depends on hormonal changes.…”
Section: Discussionsupporting
confidence: 94%
“…Hormonal stimulation and motion artifacts can cause false findings on MRM. In fact, a recently published study showed an increase in false-positive findings of 17 % when premenopausal patients are examined at a time other than during the second week of their menstrual cycle [21]. If diagnostic MRM is performed at the incorrect point in the menstrual cycle in premenopausal women or during hormone replacement therapy in postmenopausal women and if a hormonal cause for the contrast enhancement is suspected, another MRM should be performed [5,16].…”
Section: Mri-guided Lesion Markingmentioning
confidence: 99%
“…Dynamic contrast material-enhanced MR imaging is the most sensitive technique for screening high-risk women (1)(2)(3)(4) and for evaluating the extent of disease in patients with a recent diagnosis of breast cancer (5)(6)(7)(8). Despite its numerous advantages, the moderate specificity of dynamic contrastenhanced MR imaging (affected by factors such as reader experience, imaging protocol [9,10], and background enhancement [11]) can result in a substantial number of false-positive findings requiring biopsies. Reducing the number of avoidable false-positive findings at breast dynamic contrast-enhanced MR imaging could substantially decrease morbidity for patients.…”
Section: Patients and Lesionsmentioning
confidence: 99%